Some Problems of Soil Conservation and Proper Land Use in the Himalayan Region of West Bengal - Rao, V. S. (Indian Forester, 1961)
The Himalayas are the biggest and highest mountain system in the world; they are also the youngest. Having been formed by the crumpling, folding and upthrust of the sedimentary strata in a weak region of the earth’s crust by the movement of the North Asian land mass against the ancient formation of Peninsular India the mountains are steep and the rock unstable. The instability is accentuated by the high rainfall. In spite of these adverse factors the region is naturally well wooded; and the forests have held the slopes from erosion and slipping. Soil erosion, avalanches and floods are mainly caused by deforestation followed by poor land use which includes unterraced cultivation along slopes, overgrazing and setting fire to the forest. Tea cultivation has been responsible for some of the trouble, although well managed tea gardens do maintain the hill sides in a stable condition.